Ketorolac But Not Morphine Exerts Inflammatory and Metabolic Effects in Synovial Membrane After Knee Arthroscopy: A Double-Blind Randomized Prospective Study Using the Microdialysis Technique. Issue 6 (1st October 2009) - Stålman, Anders; Tsai, Jon A.; Segerdahl, Märta; Dungner, Elisabeth; Arner, Peter; Felländer-Tsai, Li
Abstract : Objective: Our aim was to study local synovial metabolism, inflammation, and subjective pain scoring after intra-articular injection of morphine, ketorolac, or placebo in knee arthroscopy. Methods: Sixty patients undergoing knee arthroscopy were randomized into 3 groups receiving morphine, ketorolac, or placebo before surgery. Microdialysis of the synovial membrane was performed in 10 patients in each group 4 hrs postoperatively. Lactate, glucose, glycerol, glutamate, and prostaglandin E2 (PGE2 ) were monitored regarding biochemical compounds and visual analog scale regarding perceived postoperative pain. Results: Ketorolac effectively attenuated postoperative PGE2 levels. Glycerol increased over time in the ketorolac group. Glutamate showed a decrease over time in both the morphine and ketorolac groups. Differences in PGE2 in the reference tissue indicated a systemic effect of ketorolac. There were no effects on subjective pain scoring (visual analog scale). Conclusions: To our knowledge, this is the first study on the local metabolic and inflammatory effect of intra-articularly administered morphine or ketorolac. For the first time, glutamate was studied in synovial tissue, and our results suggest that local release of glutamate may be important for nociception and inflammation. The effects of ketorolac on PGE2 implicates a local effect on inflammation and possibly, also nociception, but it should be remembered that 60 mg of ketorolac given intra-articularly also has a systemic effect. Release of glycerol after administration of ketorolac may indicate a toxicity of nonsteroidal anti-inflammatory drugs that must be further evaluated.